Legal Politics of The Movement and Development of The Indonesian Capital City Regarding Legal Protection of The Rights of The Community and Customary Legal Community (MHA) - Ningsih, Linda Setia; Elviandri, Elviandri; Yulianingrum, Aullia Vivi; Alhadi, Muhammad Nurcholis (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
The relocation of the National Capital (IKN) to East Kalimantan has had a significant impact on the rights of indigenous peoples (MHA), including 22 indigenous groups such as the Balik, Bajao, and Dayak tribes. Although Articles 18B and 28I of the 1945 Constitution provide the basis for constitutional recognition, their implementation is often inconsistent, resulting in the marginalization of MHA. This study uses a normative legal method with a legislative and conceptual approach. The results of the study show that agrarian legal politics have not expressly protected MHA rights, marked by the dominance of state law that ignores variations in customary law. Injustice in land conversion often occurs without adequate compensation, causing conflicts of values and interests. Gustav Radbruch's theory of legal certainty is an important framework to ensure that IKN development regulations respect customary rights clearly and predictably. Equitable legal protection is needed through formal recognition of customary land, equal compensation, and active involvement of indigenous peoples in the development process. The government needs to integrate customary law into agrarian policies to balance economic, ecological, and cultural interests. The legal pluralism approach can realize substantive justice, harmonize national development with the preservation of local values. Inclusive legal politics can make the IKN a symbol of modernization without sacrificing MHA rights, providing sustainable benefits for indigenous peoples as an integral part of the Indonesian nation.